Biomethane Production from Biogas by Separation Using Thin‐Film Composite Membranes. Issue 5 (6th March 2017) - Sedláková, Zuzana; Kárászová, Magda; Vejražka, Jiří; Morávková, Lenka; Esposito, Elisa; Fuoco, Alessio; Jansen, Johannes Carolus; Izák, Pavel
Abstract: Raw biogas obtained from a sewage plant was successfully purified by a single‐step method to a quality compatible with compressed natural gas (CNG) standards. For this purpose, thin‐film composite membranes with polyamide skin layer were evaluated at varying temperatures, pressures, feed and sweep flow rates. The wetting of the polyamide skin layer was analyzed under different experimental conditions. Optimization of the purification process resulted in a better separation than that in previous studies. The achieved CH4 and H2 S levels are conform to the required standards for commercialization in the Czech Republic. A unique feature of the presented approach, distinguishing the water‐swollen thin‐film composite membranes from polymeric membranes under dry conditions, is that the condensing water absorbs a significant amount of the minor impurities of biogas, such as H2 S. Abstract : Raw biogas from a sewage plant was purified by a single‐step separation method to a quality consistent with compressed natural gas standards. A membrane separation process based on a water‐swollen thin‐film composite membrane with polyamide skin layer was successfully applied for effective simultaneous removal of H2 S and CO2 due to the good transport properties of this membrane.